Case reportExtensive phlegmon and pyoderma gangrenosum: diagnostic difficulties - Wcisło-Dziadecka, Dominika; Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia; Arasiewicz, Hubert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Pyoderma gangrenosum (PG) is a relatively rare neutrophilic dermatosis, characterized by progressive skin necrosis. It typically has a chronic course, of unknown etiology. Pyoderma gangrenosum diagnosis can be difficult because both histopathological examination and results of additional laboratory tests are not specific and the clinical state is conclusive, as for other physicians it poses a number of diagnostic dilemmas. Therefore, this condition should be treated interdisciplinary. We present a case of a 40-year-old patient with a diagnosis of PG, which in the early stages of the disease was treated as an extensive phlegmon by physicians of other specialties and it presented a serious diagnostic as well as therapeutic problem.